Analisis Yuridis Perlindungan Hukum bagi Investor Retail terhadap Praktik Market Manipulation di Pasar Modal - Ronald Laurencius; Aturkian Laia (INDO PUBLISHING, 2026)
The increasing participation of retail investors in Indonesia's capital market hasn't been matched with adequate legal protection, making them vulnerable to market manipulation like wash trading, cornering the market, pump and dump, and spreading misleading information. This study aims to analyze the types of market manipulation, legal protection for retail investors, and the effectiveness of capital market legal instruments. The research uses a normative juridical method with a statutory and conceptual approach, based on the Capital Market Law as amended by the P2SK Law, the Financial Services Authority Law, and related regulations. The results show that market manipulation is regulated in Articles 91, 92, and 93 of the Capital Market Law. Legal protection is available through preventive and repressive mechanisms, but its effectiveness is still limited due to weak loss recovery, complex proof requirements, and low legal literacy among investors. Strengthening the class action mechanism and a technology-based market supervision system is needed to boost protection for retail investors